Behavioural and Electrophysiological Aspects of Error Processing in Alzheimer's Disease and Healthy Ageing - LACEY, ERIC ANTHONY (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2020)
An inherent aspect of healthy, non-pathological ageing is a marked decline in cognitive ability across a distributed network of functions. One feature of this reduced cognitive capacity is a diminution in the ability to monitor and assess errors. While recent advances in the field of cognitive science, and in particular electrophysiology, have made it possible to delineate several aspects of error processing, relatively little is known regarding the precise impact of ageing upon the ability to appraise errors. By combining neuropsychological and electrophysiological methodologies this thesis aims to explore this phenomenon and add to the existing body of knowledge on age-related effects on error processing. This work also sought to examine, possibly for the first time, the process of online , real-time awareness of errors in those affected by Alzheimer s disease. The impact of anxiety and depression on this error monitoring is also considered.
APPROVED
Keywords: Error Awareness; Ageing; Alzheimer's; ERN; Pe